2019
DOI: 10.1016/j.chest.2019.04.132
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Sleep Quality in COPD Is Associated With Exacerbations

Abstract: BACKGROUND: COPD increases susceptibility to sleep disturbances, which may in turn predispose to increased respiratory symptoms. The objective of this study was to evaluate, in a population-based sample, the relationship between subjective sleep quality and risk of COPD exacerbations. METHODS: Data were obtained from the Canadian Cohort Obstructive Lung Disease (CanCOLD) study. Participants with COPD who had completed 18 months of follow-up were included. Sleep quality was measured with the Pittsburgh Sleep Qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 28 publications
(29 reference statements)
2
35
1
2
Order By: Relevance
“…In the placebo group of the two largest trials on the pharmacological treatment of COPD, namely the UPLIFT and TORCH studies, neither health status nor lung function showed clinically significant changes over a 4-and 3-year interval, respectively. [26][27][28] Similar findings were documented for perceived dyspnea in the pooled Flight 1 and Flight 2 trials after one year of observation. 29 Finally, in a real-world population of COPD patients in conditions of usual care (the SALFORD study), overall dyspnea did not change significantly as it improved in 26.8% of patients but worsened in 20.9% over 12 months.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…In the placebo group of the two largest trials on the pharmacological treatment of COPD, namely the UPLIFT and TORCH studies, neither health status nor lung function showed clinically significant changes over a 4-and 3-year interval, respectively. [26][27][28] Similar findings were documented for perceived dyspnea in the pooled Flight 1 and Flight 2 trials after one year of observation. 29 Finally, in a real-world population of COPD patients in conditions of usual care (the SALFORD study), overall dyspnea did not change significantly as it improved in 26.8% of patients but worsened in 20.9% over 12 months.…”
Section: Discussionsupporting
confidence: 76%
“…18 Furthermore, in a mixed Asthma-COPD population aged over 65 years, their prevalence increases with age. 25 Of note, in the CanCOLD study 26 impaired sleep quality was associated with increased rate of exacerbations over a period of 18 months. Finally, sleep disturbances have recently been proved to correlate with respiratory symptoms, poor lung function, exacerbations during the previous year, and depression in a large COPD cohort.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Study participants underwent the standard Can-COLD assessment procedures, which provide information about patients' characteristics (age, gender, smoking history), medical history and current medications, body weight and height, and pulmonary function. Although no sleep studies were done in CanCOLD, the presence of sleep apnea was documented based on the use of continuous airway positive pressure (CPAP) and on standardized questionnaires, including the Pittsburg Sleep Quality Index [31]. Additional pre-specified measures were done including measurements of waist and hip circumferences, blood sampling to determine glucose and lipid profiles, and a computed tomography (CT) abdominal scan at 4 th /5 th lumbar vertebrae level (L4-L5) to quantify body fat distribution [21].…”
Section: Participantsmentioning
confidence: 99%
“…Actigraphy is a useful tool which is able to provide objective estimates of sleep/wake parameters similar to polysomnography and to bring more reliable information about sleep quantity and fragmentation than subjective evaluations [ 12 ]. Poor sleep quality is frequently reported in COPD [ 13 15 ] and is related to higher rates of exacerbation and hospitalisation [ 16 18 ]. Furthermore, there is evidence showing that poor sleep quality is associated with impairment of quadriceps muscle strength, exercise capacity and PADL [ 19 21 ].…”
Section: Introductionmentioning
confidence: 99%